Web-Based Financial Information System at Ibu Sri's Shop - Syahfitri, Indriyani; Ines Audi, Femy; Nurahayu, Deski; Aprilila, Dhea; Putri, Aura Iqlima; Hidayati, Nani (Devitara Innovations, 2025)
Ibu Sri's Shop is one of the Micro, Small and Medium Enterprises (MSMEs) engaged in the trade of daily necessities. Along with the growing need for efficiency and accuracy in recording transactions, this shop requires a system that can help manage finances in a structured and computerized manner. This study aims to design and implement a Web-Based Financial Information System that can help the process of recording transactions, calculating total purchases, and financial reporting at Ibu Sri's Shop more effectively and accurately. This system was developed using the PHP programming language and MySQL database with a waterfall approach as a software development method. The main features of this system include product management, recording sales transactions, and daily financial reports that can be accessed through a simple and user-friendly web interface. The implementation results show that the system built can speed up the recording process and reduce the potential for manual errors in managing store finances. In addition, this system also makes it easier for shop owners to monitor financial performance periodically without having to do manual recording. This research is expected to provide a real contribution to the digitalization of the financial system in MSMEs, especially in improving operational efficiency and data-based decision making.